Coherence and Cohesion in EFL Students’ Writing Production: The Impact of a Metacognition-based Intervention - Briesmaster, Mark; Etchegaray, Paulo (Íkala, Revista de Lenguaje y Cultura, 2017)
The objective of this Action Research study was to identify the impact of metacognitive training on the development of coherence and cohesion in the writing production, at the paragraph level, of EFL learners. The participants included 19 students from an 8th grade Chilean public school who took part in a 9-week class intervention. These classes focused on the students learning to write paragraphs in English by using metacognitive techniques such as planning, monitoring, and evaluating their own production while paying particular attention to coherence and cohesion. As instruments for data collection, L2 writing pre and post-tests were utilized. Additionally, two qualitative research techniques were employed to identify the metacognitive writing procedures used by the students before and after the metacognitive intervention. The results suggest that the EFL students used more metacognitive procedures when writing at the end of the intervention. Moreover, a slight improvement was observed in the area of cohesion.